Psoriatic arthritis with hyperuricemia: A case report - Mulianto, Nurrachmat; Ardiani Pramudya Wardhani, Irene (Journal of Pakistan Association of Dermatologists, 2023)
Introduction: Psoriatic arthritis (PsA) has a clinical picture that resembles other arthritic diseases and is accompanied by other co-morbidities such as hyperuricemia. The diagnosis of PsA needs to be established as early as possible to reduce the morbidity of the sufferer. Case: A 52 year old woman came with complaints of pain in her fingers and wrist since two years ago. The patient has a history of psoriasis vulgaris for three years but is not taking medication regularly. The patient had his complaints checked, stated that he had gout, complaints improved but came and went. On examination of the dermatological status of the posterior truncus and manus region bilaterally and the lower extremity region, multiple erythematous papules and plaques were seen with thin scales on it. On the 2nd and 3rd digits of the right manus and 3rd digit of the left manus there is edema. Dermoscopic examination, bilateral manus x-ray and bilateral genu support the picture of PsA. The blood laboratory examination revealed hyperuricemia. Based on The Classification Criteria for PsA (CASPAR) a total of 5 points was obtained. Patients were given methotrexate tablets 7.5 mg per week orally, folic acid, sodium diclofenac, zinc and narrow band ultraviolet B phototherapy (NBUVB) 330mj/cm2 per week which was increased by 10% from the minimal erythema dose (MED) per session with a satisfactory response. Discussion: The diagnosis of PsA can be established by CASPAR criteria, namely assessing a history of psoriasis, onychodystrophy, negative results on rheumatoid factor, dactylitis and new bone formation near joints. In this case, 5 CASPAR points were obtained so that the differential diagnosis of rheumatoid arthritis and gout arthritis could be ruled out.